The presence of Forensic Medicine as a discipline in Law courses: analysis of its importance for Criminal Procedural Law and the expertise of the Brazilian justice system, alluding to the Isabella Nardoni case (Research, Society and Development, 2021)
Objective: The purpose of this article is to analyze the presence of the discipline of Legal Medicine (ML) in Higher Education Institutions (HEIs) in the northeast region of Brazil, as well as to better elucidate the positive influence that ML has in solving concrete cases in the process penal. Methodology: Through the electronic database of the Ministry of Education (e-MEC), all Northeastern HEIs with degrees in Law were collected, followed by the consultation of the curriculum on the website of each institution. The presence of the ML discipline in the curricular matrix, its workload, mandatory teaching and the period in which it is taught were evaluated. In addition, the case of the “Nardoni couple” was analyzed, discussing the necessity of ML to reach the real procedural truth. Results: 264 colleges were included, where only 91 have an exclusive subject for teaching it. Among the colleges in which it is taught, its mandatory presence is present in only 45.7% of graduations. The average workload was 49.7 class hours, representing only 1.2% of the total hours of the curriculum structure. Conclusion: It is possible to verify that the teaching of Legal Medicine is not in preponderance in the HEIs in the Northeast, it is up to the Bachelor of Laws to seek further training on the subject.